Paradoxical Permaculture? - Finkill, Guy (2020)
Permaculture purportedly offers a range of solutions to the negative externalities that arise from the dominant processes of monoculture crop cultivation and industrialised food production. This thesis identifies the discursive practices used by Swedish permaculturists to communicate and promote the advantages of permaculture over the incumbent industrial food production regime.